2017
DOI: 10.1111/pcn.12483
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial sonography in idiopathic REM sleep behavior disorder and multiple system atrophy

Abstract: Some iRBD patients had basal ganglia hyperechogenicity that was similar to that observed in MSA, which may represent another possible convert direction. The present study further confirmed iRBD as a prodromal stage of synucleinopathy. TCS could detect subclinical changes and thus might provide useful markers for identifying individuals at increased risk for developing a synucleinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…TCS can detect a hyperechogenicity of the SN in PD, while the lack of hyperechogenicity in the SN in other movement disorders is the basic principle underlying the ability of TCS to differentiate PD from other movement disorders. Besides, previous studies have shown that the basal ganglia may show hyperechogenicity of TCS in MSA [ 36 ]. In comparison, the lack of hyperechogenicity in the basal ganglia of patients with PD indicates that the SN findings combined with basal ganglia echogenicity can better distinguish patients with PD from those with other movement disorders, such as MSA.…”
Section: Discussionmentioning
confidence: 99%
“…TCS can detect a hyperechogenicity of the SN in PD, while the lack of hyperechogenicity in the SN in other movement disorders is the basic principle underlying the ability of TCS to differentiate PD from other movement disorders. Besides, previous studies have shown that the basal ganglia may show hyperechogenicity of TCS in MSA [ 36 ]. In comparison, the lack of hyperechogenicity in the basal ganglia of patients with PD indicates that the SN findings combined with basal ganglia echogenicity can better distinguish patients with PD from those with other movement disorders, such as MSA.…”
Section: Discussionmentioning
confidence: 99%
“…Because an important percentage of patients initially diagnosed with iRBD develop PD or other synucleopathies, this technique should be a useful tool to predict conversion of iRBD to PD and other neurodegenerative diseases. SNH was significantly more frequent in patients diagnosed with iRBD than in controls [ 21 , 48 , 49 , 50 ], although less frequent than in patients diagnosed with PD [ 48 , 51 ], and had a similar frequency than that reported in MSA patients [ 51 ]. SNH was more frequent in iRBD patients with than in those without mild motor abnormalities [ 24 ].…”
Section: Search Strategymentioning
confidence: 88%
“…Researchers also found hyperechogenicity in the basal ganglia in 50% (11 out of 22) of iRBD patients compared to 10% (2 out of 21) of controls (Li, Xue, et al, 2017). In another study, researchers reported on their investigation of echogenicity in the brainstem raphe nuclei in relation with depression in 72 iRBD patients (Vilas et al, 2015).…”
Section: Transcranial Sonographymentioning
confidence: 94%
“…Several authors reported substantia nigra hyperechogenicity in patients compared to controls (Iranzo et al, 2010;Iwanami et al, 2010;Shin et al, 2013;Stockner et al, 2009;Vilas et al, 2015), which was lower or of similar amplitude than in PD patients (Iwanami et al, 2010;Shin et al, 2013). The proportion of patients with pathological substantia nigra hyperechogenicity was higher in iRBD patients (32-63%) than in controls (5-29%) (Iranzo et al, 2010;Iwanami et al, 2010;Li, Xue, et al, 2017;Rupprecht et al, 2013;Shin et al, 2013;Stockner et al, 2009;Vilas et al, 2015).…”
Section: Transcranial Sonographymentioning
confidence: 99%
See 1 more Smart Citation